2019
DOI: 10.1186/s12889-019-7489-3
|View full text |Cite
|
Sign up to set email alerts
|

Health outcomes of the July 14, 2016 Nice terror attack among hospital-based professionals and students: the « ECHOS de Nice » health survey protocol

Abstract: Background The terror attack of July 14, 2016, in Nice, France, resulted in 86 deaths, including children, and several hundred wounded, with a major psychological impact on the population. Hospital staff had to cope with exceptional circumstances which made them vulnerable to detrimental effects on their own health. This paper describes the method that was selected for the survey entitled “ ECHOS de Nice 14 Juillet ” which aimed to assess the impact of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…Moreover, self-assessment may have resulted in inaccuracy in individual diagnosis. Furthermore, the interview period lasted 4 months, and encompassed the date of the subsequent terrorist attack in Nice (14 July 2015) [ 52 ]. This attack may have led to an increase in the intensity of PTSD symptoms in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, self-assessment may have resulted in inaccuracy in individual diagnosis. Furthermore, the interview period lasted 4 months, and encompassed the date of the subsequent terrorist attack in Nice (14 July 2015) [ 52 ]. This attack may have led to an increase in the intensity of PTSD symptoms in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…( 8 ) Due to the nature of nursing work experienced heavy workload, working long hours, night shifts and risk of exposure with infectious disease, the most studies on burnout were focused on nurses that sometimes remain as significant concerns, affecting not only work office but also individual life and sometimes can lead to increased risk of developing mental and physical health problems. ( 9 ) Since an outbreak of COVID-19 as an unknown disease that causes severe respiratory infectious disease and similar experience on SARS and MERS, nursing managers need to pay more attention to frontline nurses' burnout in association with their experiences of a nationwide MERS and SARS outbreak to be able to manage the conditions. ( 10 ) Thus, the aim of the present study is to assess and compared burnout level between frontline nurses and other nurses during an outbreak of COVID-19 and to identify influencing factors in order to provide basic information for lowering and preventing the level of burnout.…”
Section: Introductionmentioning
confidence: 99%
“…By comparison, a study revealed that the participation rate was 25% among firefighters in Paris and affiliated volunteers following the November 2015 Paris attack; but this rate could not be assessed and was probably much lower among health professionals [ 15 ]. This rate may have resulted in bias, as discussed elsewhere [ 23 ]. Indeed, unexposed personnel may have felt unconcerned by the survey and not considered it worthwhile to participate: thus, only 1014 among all the employees chose to connect to the web questionnaire, and 804 completed it, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This was a cross-sectional, multi-centre, observational study. The detailed description of the study protocol has been described elsewhere [ 23 ].…”
Section: Methodsmentioning
confidence: 99%